Ficção e fruição de paisagens de Oitocentos: entre o Porto e Vila Real, por Edward Quillinan - Abreu, Carmen Matos (CEM – Cultura, Espaço & Memória, 2021)
The Edward Quillinan’s novel The Sisters of the Douro highlights a set of Heritage Landscapes confined by the banks of the Douro river, as well as all the anthropic process about customs and manners of the Douro inhabitants during the 2nd French invasion of northern Portugal. On the narrative stage between Porto and Vila Real, the text is deeply enriched by heritages of urban or country landscapes observed along the way, describing building and topographic details, including flora and fauna. Imposed by the romantic literary aesthetics, the reader also notices about a loving plot of two Portuguese young women from the Douro and two English officers, pages where deep and original cultural and anthropic perspectives are developed. This novel is generally considered a historic document of the Portuguese Patrimony of the nineteenth century. For this reason, and in accordance with the cultural and geographical framework provided by literary realism, it is acceptable that all those heritage values can be prospectively collected and considered.